A simple and accurate method for calibrating the oscillation amplitude of tuning-fork based AFM sensors - Liu, Jinquan; Callegari, Andrea; Stark, Martin; Chergui, Majed (Ultramicroscopy, 2008)
We have developed a simple and accurate method for calibrating the amplitude of vibration of quartz tuning fork sensors commonly used in atomic force- and near field optical-microscopy. Unlike interferometric methods, which require a complex optical setup, the method we present requires only a simple measurement of the electro-mechanical properties of the tuning-fork oscillator and can be performed in a matter of minutes without disturbing the experimental setup. Comparison with interferometric methods shows that an accuracy of better than few percent can be routinely achieved.